2015
DOI: 10.1002/adsc.201401158
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysis of Cycloastragenol by Syncephalastrum racemosum and Alternaria alternata to Discover Anti‐Aging Derivatives

Abstract: Cycloastragenol is ac ycloartane-type triterpenoid with significant telomerase-activating activities.Inthis paper, the biocatalysisofc ycloastragenol by two strains of filamentous fungi, namely Syncephalastrum racemosum AS 3.264 and Alternaria alternata AS 3.4578, was investigated. Scaled-up biotransformation reactions yielded 27 metabolites. Their structures were established on the basis of extensiveN MR and HR-ESI-MS data analyses,a nd 18 of them are new compounds.T he twof ungal strains exhibited distinct b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
4
9
0
Order By: Relevance
“…In addition, compounds 7 and 8 were the rearrangement products of CCG resulting from the cleavage of 9,19-cyclopropane ring followed by methyl migration. This unique transformation was reported previously in the biotransformation of CA and CCG by Cunninghamella blakesleeana NRRL 1369, Syncephalastrum racemosum AS 3.264 and Alternaria alternata AS 3.4578 (Bedir et al, 2015;Feng et al, 2015;Kuban et al, 2010;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In addition, compounds 7 and 8 were the rearrangement products of CCG resulting from the cleavage of 9,19-cyclopropane ring followed by methyl migration. This unique transformation was reported previously in the biotransformation of CA and CCG by Cunninghamella blakesleeana NRRL 1369, Syncephalastrum racemosum AS 3.264 and Alternaria alternata AS 3.4578 (Bedir et al, 2015;Feng et al, 2015;Kuban et al, 2010;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, downfield shift of C-3 signal suggested that an oxygen bridge involving C-3 atom was present in the framework. Resemblance of the spectral data of 4 with those of previously reported compounds (Feng et al, 2015) together with the long-distance correlation of the quaternary carbon at 88.3 ppm with H-3 (d 3.73) provided evidence for the oxygen bridge between C-3 and C-10 carbons. The orientation of 3(10)epoxy bridge was confirmed by inspecting the ROESY spectrum of 4 and calculating its minimized energy conformer by MM2 molecular mechanics program.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Previously, CA was suggested to ameliorate the decrease in Nrf-2 expression caused by TNF-α treatment in vascular smooth muscle cells. In another study, 50 μM CA slightly increased the Nrf-2 transcription in HepG2 cancer cells (Feng et al, 2015), which has much higher intrinsic telomerase expression compared to normal human cells (Sakaguchi et al, 2017; Watanabe et al, 2011). In this study, we found that CA not only increased Nrf-2 protein expression but also enhanced the nuclear localization of Nrf-2, leading to ARE-promotor activity and consequently increasing the levels of cytoprotective enzymes such as HO-1, GR, and GCLC to protect cells against oxidative stress ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 90%
“…Biotransformation, as an alternative method for structural modification, catalyzes many important reactions, especially in structurally complex natural products [16]. This method exhibited many advantages such as stereo-or region-selectivity, mild reaction conditions and avoiding complex protection, and deprotection steps over chemical synthesis [17][18][19].…”
Section: Introductionmentioning
confidence: 99%